Differential microRNA expression in the SH-SY5Y human cell model as potential biomarkers for Huntington’s disease - Belkozhayev, Ayaz; Niyazova, Raigul; Kamal, Mohammad Amjad; Ivashchenko, Anatoliy; Sharipov, Kamalidin; Wilson, Cornelia M. (Frontiers in Cellular Neuroscience, 2024)
Huntington's disease (HD) is caused by an expansion of CAG trinucleotide repeat in the HTT gene, the exact pathogenesis of HD currently remains unclear. One of the promising directions in the study of HDs is to determine the molecular mechanism underlying the development and role of microRNAs (miRNAs). The purpose of this study was to identify the profile of miRNAs in a HD human cell line model as diagnostic biomarkers for HD. To study HD, the human SH-SY5Y HD cell model based on the expression of two different forms -pEGFP-Q23 and pEGFP-Q74 of HTT. The expression of Htt protein was confirmed using aggregation assays combined with immunofluorescence and Western blotting methods. miRNA levels were measured in SH-SY5Y neuronal cell model samples of stably expressing Q23 and Q74 using the extraction-free HTG EdgeSeq protocol. A total of 2083 miRNAs were detected, and 354 (top 18 miRNAs) miRNAs were significantly differentially expressed (DE) (p < 0.05) in Q23 and Q74 cell lines. A majority of the miRNAs were downregulated in the HD cell model. Moreover, we revealed that six DE miRNAs target seven genes (ATN1, GEMIN4, EFNA5, CSMD2, CREBBP, ATXN1 and B3GNT) which play important role in neurodegenerative disorders showed significant expression differences in mutant Htt (Q74) when compared to wild-type Htt (Q23) using RT-qPCR (p < 0.05 and 0.01). We demonstrated the most important DE miRNA-mRNA profiles, interaction binding sites and their related pathways in HD using experimental and bioinformatics methods. This will allow the development of novel diagnostic strategies and provide alternative therapeutic routes for treating HD.